The Influence of Varying Gingival Display of Maxillary Anterior Teeth on the Perceptions of Smile Aesthetics. (December 2020) - Sybaite, J; Sharma, P; Fine, P; Blizard, R; Leung, A
Abstract: Objectives: The aim of the study was to investigate the influence of gingival display on perceived smile aesthetics and to compare aesthetic gingival display preference amongst dental professionals and lay people. Methods: This cross-sectional study was based on the analysis of quantitative data collected via questionnaires. Two sets of digitally altered smile images with variations of gingival amount and architecture displays were produced. Ranking order scale was used to record aesthetic preferences, from the most attractive to the least attractive. Results: There were 124 respondents (60 lay people, 32 general dentists [GDPs] and 32 orthodontists). Average smile line, tangent to the zeniths of maxillary anterior teeth, was found to be the most attractive gingival amount (53.2%, χ 2 = 144.15, p < 0.045) amongst lay people, GDPs and orthodontists. High smile line was ranked as the least attractive amount amongst all respondents (88.7%, χ 2 = 359.37 p < 0.002). Class III gingival outline, where all gingival levels are symmetrical and in line, was found as the most attractive gingival architecture (65.3%, χ 2 = 10.87 p < 0.001). Conclusion: No particular amount of gingival display is universally perceived as attractive although high smile lines are generally disliked. Class III gingival architecture is the most preferred gingival archetype when excessive amount of maxillary gingiva is exposed. Clinical significance: A general acceptance to smile line variations demonstrates that the harmony amongst all smile components is more important than merely focusing on a single ideal smile constituent. However, when designing the smile with an inherent high lip line, a Class III gingival architecture might be more preferable since it reduces the negative impact of excessive gingival display.